Pension fund capitalism in Europe: institutional organisation and governance of Finnish pension insurance companies - Sorsa, V (2011)
Pension capital is the single largest block of capital in the global domain of finance and a transformative social force. However, the studies on pension fund capitalism have been geographically limited. Although vast pools of pension capital have been generated outside the Anglo-American institutional environments, we still have little knowledge on the social construction of pension fund capitalism outside that context. The purpose of the study is to develop theoretical-methodological tools for studying the institutional differences in pension fund investments with habitual institutionalist theory at the level of organisation fields, and to apply these tools in an empirical case study that has theoretical relevance concerning the recent financialisation of European pension provision. The case study is focussed on the field of Finnish pension insurance companies that execute the nationally mandatory partly funded TyEL pension scheme. The case study includes a single case analysis at the organisation field level with embedded case analyses on the investment processes in two companies. The study is based on multiple sources of textual and interview data gathered and analysed with content analysis. It is argued that the institutional life of Finnish pension insurance company investments illustrates divergence from the Anglo-American pension fund capitalism and has reinforced elastic institutional solutions especially in domains of governance and regulation even under Europe-wide financialisation pressures. The Finnish case shows that there are alternative institutional solutions for various domains of pension fund capitalism, but the strong Europe-wide trends have all characterised recent institutional change in the TyEL field as well. It is concluded that although the European shift towards pension fund capitalism with the generation of increasingly independent portfolio investors with increasingly principle-based regulation and risk-based supervision has not necessarily implied strong institutional convergence, the European pension investors are likely to share a number of common questions in the future.